1989
DOI: 10.1152/jappl.1989.66.6.2546
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to low-dose endotoxin in awake sheep

Abstract: Dose response and tolerance to a small intravenous dose of Serratia marcescens lipopolysaccharide (LPS) were studied in awake sheep. Core temperature significantly increased after a dose of 0.002 micrograms/kg; changes in pulmonary arterial pressure, pulmonary vascular resistance, plasma thromboxane B2, and circulating leukocyte concentration occurred after 0.02 micrograms/kg; plasma 6-keto-prostaglandin F1 alpha increased after 0.2 micrograms/kg. Development of acute tolerance was studied by injection of S. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Previous studies have shown that tolerance develops with repeated doses of endotoxin over a period of days (15)(16)(17). However, we found no marked differences between the three LPS treatments in both the temperature and cortisol responses.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have shown that tolerance develops with repeated doses of endotoxin over a period of days (15)(16)(17). However, we found no marked differences between the three LPS treatments in both the temperature and cortisol responses.…”
Section: Discussioncontrasting
confidence: 79%
“…Pregnenolone, progesterone, and allopregnanolone were measured in plasma and the brain. Experiments were repeated three times between 12 and 20 d of age to allow us to determine whether the responses were attenuated by repeated exposure to LPS, as has been observed in adult animals (15)(16)(17). Our results show that large changes in peripheral and central concentrations of allopregnanolone and increased sleep occur on exposure to LPS in the newborn lamb, with no evidence of tolerance.…”
mentioning
confidence: 53%
“…All of these responses were attenuated after subsequent LPS treatments, but fetuses remained mildly hypoxemic at the conclusion of the 5-d protocol. Attenuation of responses to repeated LPS exposure has been described previously (34,35), and may be due to down-regulation of the LPS receptor CD14 (36). The fetal hypoxemia and metabolic acidosis after LPS are likely due to placental dysfunction as LPS, albeit at higher doses, increases umbilico-placental vascular resistance (37).…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the ablated effect on TNF-and IL-6, the response of both activin A and follistatin was reduced following LPS treatment of an identical dose administered 5 days after an initial challenge. The nature of how these proteins form part of the tolerance mechanism has not been elucidated; tolerance is readily demonstrable in mature sheep (Whyte et al 1989) and is also presumed to occur in immature animals. Of interest will be to establish if the diminished release of activin/follistatin is subject to a recovery in responsiveness, as in rats there is an initial refractory period to repeated LPS stimulation which disappears after some weeks and after which a full response to LPS is observed again (Sanchez-Cantu et al 1989).…”
Section: Discussionmentioning
confidence: 99%